2013
DOI: 10.1039/c3ta10329c
|View full text |Cite
|
Sign up to set email alerts
|

One-pot, large-scale synthesis of magnetic activated carbon nanotubes and their applications for arsenic removal

Abstract: We report a one-pot method to synthesize magnetic iron oxide/CNT composites (MI/CNTs) based on as-prepared CNTs (APCNTs) using KOH activation. MI/CNTs have high specific surface area, good dispersion and magnetic properties, making them promising for use as adsorbents for arsenic removal. The results of this work are highly significant for large-scale applications of APCNTs containing Fe catalytic particles without the need for prior purification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(52 citation statements)
references
References 33 publications
0
52
0
Order By: Relevance
“…Wang et al (2011) removed cobalt from aqueous solution using magnetic MWCNT-iron oxide composites. Ma et al (2013) reported a one-pot method to synthesize magnetic iron oxide-CNT composites for arsenic removal. Yang et al (2013) showed the adsorption of naphthalene and its derivatives to magnetic MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2011) removed cobalt from aqueous solution using magnetic MWCNT-iron oxide composites. Ma et al (2013) reported a one-pot method to synthesize magnetic iron oxide-CNT composites for arsenic removal. Yang et al (2013) showed the adsorption of naphthalene and its derivatives to magnetic MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Controlling the size, composition, and shape of the metal (oxide) nanoparticles, however,i sl imited with these methods. [1][2][3] Controlling the size, composition, and shape of the metal (oxide) nanoparticles, however,i sl imited with these methods.…”
mentioning
confidence: 99%
“…Commonly appliedc atalyst synthesis methods, such as incipient wetness impregnation and precipitation, are often used to obtain supported catalysts for industrial use. [1][2][3] Controlling the size, composition, and shape of the metal (oxide) nanoparticles, however,i sl imited with these methods. Colloidal synthesis has been successfully appliedt oo btain well-defined model catalysts suitable for fundamentals tudies.…”
mentioning
confidence: 99%
“…Functionalizing the surfaces of these carbon-based 3D structures with metal oxides can create an attractive adsorbent for water purification. Many technologies for the removal of arsenic from water that use carbon-based nanomaterials functionalized with the metal oxide magnetite (Fe3O4) have been reported [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%